Osteoma of the Medial Wall of the Maxillary Sinus: A Primary Cause of Nasolacrimal Duct Obstruction and Review of the Literature. (11th November 2014) - Saratziotis, Athanasios; Emanuelli, Enzo
Abstract : A 74-year-old male patient presented to the outpatient department with left-sided epiphora and chronic dacryocystitis, without any history of head trauma or previous nasal or paranasal sinuses surgery. No abnormalities were noted at the time with the use of nasal endoscopy. The computed tomography scan however revealed an osteoma of the medial wall of the left maxillary sinus. An endonasal endoscopic dacryocystorhinostomy (DCR) with osteoma removal by using a drill with temporary silicone stenting of the nasolacrimal duct system was performed. Due to a granuloma formation at the DCR-window site 2 months postoperatively a revision-DCR was performed and the new window remained patent at control 6 months after surgery.